The effect of abdominal bracing on respiration during a lifting task: a cross-sectional study - Martin Sembera; Andrew Busch; Alena Kobesova; Barbora Hanychova; Jan Sulc; Pavel Kolar (BMC, 2023)
Abstract Background Abdominal bracing is a maneuver widely used by rehabilitation specialists and sports trainers to improve spinal stability. This study aimed to investigate how lifting tasks with and without abdominal bracing affect the respiratory function of the diaphragm. Methods M-mode ultrasonographic assessment of diaphragmatic motion combined with spirometry was performed on 31 healthy adults. Participants were asked to breathe continuously whilst lifting a load with spontaneous abdominal muscle contraction (natural loaded breathing) and abdominal bracing (AB loaded breathing). Results Pearson's correlations revealed strong correlations between ultrasonography and spirometry measures (p < 0.001) for all types of breathing: tidal breathing (r = 0.709, r 2  = 0.503), natural loaded breathing (r = 0.731, r 2  = 0.534) and AB loaded breathing (r = 0.795, r 2  = 0.632). Using paired-samples t-tests, the natural loaded breathing ultrasonography revealed more caudal diaphragm positions during inspiration (p < 0.001) but not during expiration (p = .101). Spirometry demonstrated lower lung volumes (L) at the end of inspiration and expiration (p < 0.001), with no changes in total lung volume (p = 0.06). The AB loaded breathing ultrasonography revealed more caudal diaphragm positions during inspiration (p = 0.002) but not during expiration (p = 0.05). Spirometry demonstrated lower lung volumes at the end of inspiration (p < 0.001), expiration (p = 0.002), and total lung volumes (p = 0.019). Conclusion This study demonstrated that abdominal bracing performed during a lifting task reduces lung volume despite an increase in diaphragmatic motion. Diaphragm excursions strongly correlate with lung volumes even under postural loading. Trial registration The study was prospectively registered on 8 April 2021 at ClinicalTrials.gov with identification number NCT04841109.